Problematika Implementasi Undang-Undang Nomor 6 Tahun 2014 tentang desa di Kabupaten Sidoarjo - Ahmad Mahyani; Slamet Suhartono; Dwi Putri Sartik; Johanes Dipa Widjaya (UIR Law Review, 2019)
The state recognizes and respect the Village as a legal community unit that has the authorithy to regulate and manage gonverment affairs and the rights of origin and traditional autonomous. In the context of recognition and respect, since the independence of Indonesia several regulation have been enacted which from the legal basic for implementing village governance. The enactment of Law number of 2014 concerning villages and their implementing laws and regulations also bring legal consequences to the administration of the village administration, including the restructuring of village apparatus, the preparation of village development plans and other legal consequences. This research focuses on the implementation of law no 6 of 2014 specifically the preparation of the village budget and the orderly administration of the village so that it can be seen the problems experienced by the village government.